Assessment of Crop Water Demand in Orissa - Singandhupe, R B; Sethi, Ranu Rani; James, B K; Kumar, Ashwani (Journal of Agricultural Engineering, 2007)
The study aims to assess the season wise total water available through rainfall and the evaporative demand of crops and then to evaluate deficit/surplus water available for further use. The district- wise monthly evaporative demand of Orissa was calculated as per the globally accepted method of FAO 56 - Penman Monteith. The results revealed that the evaporative demand (ETo) is greater than water supply through rains. The annual water available through rain is 1492.8 mm against the evaporative demand of 1657.8 mm; hence there was deficit of only 9.94 %. In non-coastal districts of Orissa, excess rainfall (649.62 to 841.9mm) over the crop evaporative demand (580.5 to 647.2mm) is higher as compared to coastal districts. When season wise crop evaporative demand and availability of rainwater as supply is concerned, in most of the districts, the availability of water during kharif season (June to October) through rainwater is quite high than the crop evaporative demand. During rabi and summer season (November-March and April-May) it is deficit. Rice being a major crop of this state consumes more water, its substitution with oilseed and pulse crops which are less water requirement, is highly beneficial to increase overall income of the farmers and also save good amount of water.